KAJIAN KESESUAIAN LAHAN DUSUN TARAET DESA BETUMONGA DALAM KERANGKA PERENCANAAN KAWASAN WISATA LANSKAP PESISIR MENGGUNAKAN SOFTWARE ArcGIS - Agung Hallel Tasilipet; Debora Budiyono; Hendra Kurniawan (BUANA SAINS, 2026)
Planning coastal tourism landscape areas is an effort to improve the community’s economy. Planning for tourist destinations must take into account land suitability and physical conditions to produce safe, comfortable, and sustainable tourism. This research aims to analyze ten indicators of land suitability, namely Topography, Beach Width, Beach Type, Water Base Material, Beach Depth, Water Brightness, Beach Slope, Dangerous Biota, Availability of Fresh Water, and Vegetation, based on Land Cover type and criteria. This research was carried out in the coastal area of Taraet Hamlet, Betumonga Village, North Sipora District, Mentawai Islands Regency. The analytical methods used in this research are field observations, satellite imagery, and DEM data processed using ArcGIS. Collecting respondents' Hazardous Biota and Fresh Water Availability through FGDs. Based on the results of the analysis, it shows that physically the area has great potential to be developed as a coastal tourism area, with the classification of the Suitable zone as a tourist area covering an area of 554.29 Ha (98%) and the Suitable Zone covering an area of 11.63 Ha (2%).